UMP celebrates SPM leavers - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
KUANTAN, 8 June 2023 - Universiti Malaysia Pahang (UMP) shared the thrill with students at 13 selected schools around Pahang to celebrate the success of Sijil Pelajaran Malaysia (SPM) students who received excellent results.